Synthesis, Characterization and Thermal Behaviour of Manganese(II), Cobalt(II), Nickel(II), Copper(II) and Zinc(II) Complexes of Vanillin - ZHAO, GUOLIANG (Asian Journal of Chemistry, 2010)
Five solid complexes of transition metal acetate with vanillin of the general formula [ML2(H2O)2], where M = Mn(II), Co(II), Ni(II), Cu(II), Zn(II), HL = vanillin i.e., 4-hydroxy-3-methoxy benzaldehyde (C8H8O3) have been synthesized in boiling water system and characterized by elemental analysis, IR spectra and conductivity measurements. The M(II) ion in the complexes coordinates with two vanillin ligand via four oxygen atoms of the phenol hydroxy groups and methoxy groups and two water molecule via their two oxygen atoms. Their coordination number are six. The thermal behaviour of these complexes has been studied by TG and DTA. These complexes show two, three or four steps weight loss upon heating up to 450 ºC and show almost similar mode of decomposition. The residues after heating correspond to metal oxide. Nickel forms the most thermally stable complex.